Correction: A Historical Overview of the Classification, Evolution, and Dispersion of Leishmania Parasites and Sandflies. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2016)
[This corrects the article DOI: 10.1371/journal.pntd.0004349.].